Outcome of Surgically Treated 79 Patients of Hepatic Hydatidosis: A Single Center Tertiary Care Hospital Experience in Bangladesh (Journal of Surgical Sciences, 2020)
Background: Proper patient selection for most appropriate treatment option for hepatic hydatid is crucial to ensure successful treatment outcome. Chemotherapy, newer approaches, like PAIR procedure, (puncture, aspiration, injection and reaspiration) laparoscopy are available. As the indications for these approaches are restricted, surgery remains the key treatment strategy with hope for complete cure. Radical surgical excision coupled with chemotherapy and long-term aggressive chemotherapy for partially resected ensures lowest morbidity and mortality.Methods: This cross sectional observational study of 15-year single-institution experience, intended to further validate different surgical procedures in management of hydatid disease of liver and its outcome. Patients were randomly selected irrespective of their age, sex and mode of presentation. Different preferred surgical treatment modalities, perioperative complications, recurrences, and length of hospital stay were retrospectively analyzed.Result: The study was carried out on 79 Bangladeshi patients diagnosed hepatic hydatidosis, treated surgically from January 2002 to December 2017 in BIRDEM General Hospital. Among them was no anastomotic leakage or mortality in the immediate postoperative period in our series.Conclusion: This study revealed, proper case selection and consideration of risks-benefits, indicationscontraindications for each case of Hydatid cyst of liver, for making a decision for type and timing of surgery is key to successful outcome. Surgery is the mainstay of treatment strategy. Radical surgery is key to effective and successful outcome, ensures better quality of life and prevents recurrence of the disease.Journal of Surgical Sciences (2018) Vol. 22 (2) : 118-124